(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In recent years, fire automation has entered the artillery area with full force, which together with the introduction of visualization from various sources on the battlefield, has led to changes in the methods for determining the data for firing at the targets of the opposing forces. Real combat operations have become a springboard for practical testing of various procedures in this direction. The presence of an enemy seeking to counter artillery fire additionally, through active actions, has reduced the time for performing fire tasks and imposed the need for changes in the determination of fire data for hitting targets of different nature. Historically, this is another step towards improving the effectiveness of fire and maneuver of artillery fire support means, especially for older models, which are still used in the space saturated with artillery systems of modern conflicts.